Influence of School Agricultural Farms on Academic Performance in Agriculture as a Subject In Secondary Schools. - Machisu, Vitalis (JOOUST, 2023)
Agricultural education contributes significantly to political, social and economic aspects of development. The overall objective of the study was to understand the influence of school agricultural farms on academic performance in agriculture as a subject in secondary schools in Hamisi sub-county. The specific objectives were: to characterize school agricultural farms, to assess the influence of students’ perceptions towards school agricultural farms on academic performance in agriculture as a subject and to evaluate the influence of school agricultural farms on academic performance in agriculture as a subject in secondary schools in the study area. This study used Research conceptual model that advances the opinion that teaching is a concept with an interplay that employs sets of variables to realize its objectives. Hamisi sub- County has 50 secondary schools offering agriculture as an examinable subject at KCSE, with 2800 students, 50 principals and 50 agriculture teachers purposive sampling was used to collect data from principals and teachers while simple random sampling was used to collect data from students. School agricultural farms in Hamisi sub-county have been in operation for an average of 23 years, with 91.7% having less than five acres 54% and are managed by teachers. 87.5% of the farms are within walking distance from classrooms. The linear regression model, shows that students’ perception towards school agricultural farms had a significant effect on their academic performance (Wald=10.907, p=.001) presence of schools agricultural farms increased performance in agriculture by 0.21(β2 = 0.21; p < 0.05). It was concluded that perception of students and teachers influence learning and teaching of agriculture which has significant effects on their academic performance. The study recommended further studies on management of school agricultural farms to enhance student performance in the subject. Similarly, seminars for teachers should be intensified to encourage cultivation of positive perception toward teaching and learning agriculture in agricultural farms.
Keywords: School Agricultural Farms; Agriculture as a Subject In Secondary Schools.